Taking Place: Reflections from the Fieldworker - Staničić, Aleksandar; Havik, Klaske; Velevski, Slobodan; Santiago Baptista, Luís (Writingplace, 2023)
This issue of Writingplace Journal moves into the field, exploring the moment when reflection turns into action, and questions how knowledge produced via research is appraised and applied on the ground. In the articles, authors reflect upon their concrete experiences where insights regarding the city and its narratives have been made operational. Understanding the urban as a complex expression of social, historical, material, spatial and temporal relations between people and their built environment, we argue that this comprehension of places demands and envisions action, by which active and transformative processes take place in the real world. Fieldwork is in this sense both research and event, both investigative process and performative project.